Efektivitas Sediaan Balm Berbasis Minyak Jelantah Termurnikan terhadap Xerosis pada Tumit: Efektivitas Sediaan Balm Berbasis Minyak Jelantah Termurnikan terhadap Xerosis pada Tumit - Oneayu One; minda sari lubis; rafita yuniarti; Zulmai Rani (LPPM Universitas Abdurrab, 2025)
Xerosis is a skin condition characterized by decreased water content in the stratum corneum, leading to dryness, scaling, roughness, and pruritus, which may cause discomfort and increase the risk of infection. Purified used cooking oil has potential as an alternative emollient that is economical and environmentally friendly. This study aimed to evaluate the quality characteristics of purified used cooking oil, formulate a skin balm preparation, and assess its effectiveness in treating heel xerosis. This study employed a quantitative experimental method, including purification of used cooking oil, quality characterization based on national standards, toxicity testing using the Brine Shrimp Lethality Test(BSLT), formulation of skin balm with concentrations of 0%, 9%, 18%, and 27%, as well as physical stability and effectiveness evaluation using a skin analyzer. The results showed that the purified used cooking oil met quality standards. The skin balm preparation demonstrated good stability in terms of organoleptic properties, homogeneity, pH, spreadability, and adhesiveness during storage and cycling tests. Effectiveness testing indicated an increase in skin moisture corresponding to higher oil concentrations, with the highest improvement observed at 27% concentration (73.9% water content and 69.2% oil content). In conclusion, the skin balm formulation based on purified used cooking oil is effective in improving skin moisture and treating heel xerosis.